Displacement decisions during wartime: Surveys from Cote d'Ivoire, 2010-2011 - Justino, Patricia (UK Data Service, 2018)
Dataset resulting from 700 questionnaires administered to heads of households living in PK18, a neighbourhood of Abidjan that was shelled by government forces during Cote d’Ivoire’s electoral crisis in 2010-2011. The research focuses on displacement decisions in PK18, a poor and remote suburb of northern Abidjan, during the 2011 post-election crisis when the area was subject to shelling, street-to-street fighting and targeted violence. The most intense period of violence lasted less than a week in February 2011, and in that week PK18 experienced massive population displacement. Displacement is not a simple response to a single threat. Many competing threats to life and possessions exist in such contexts of wartime displacement decisions, and the decision is not just between life and possessions but also between, for instance, threats to life if staying and other threats to life if leaving. Displacement decisions are about using the resources of the household and its network to manage all of those competing threats for household members, within a context of very limited information. As such displacement decisions are far from a straightforward, if difficult, decision and are often extremely complex. Violent conflict results in enduring constraints to development. However, violence has an instrumental role beyond destruction. It is used strategically by political actors to promote social transformation. One way transformation takes place is through the emergence of local governance structures in places where the government is absent or heavily contested. These structures will affect significantly the living conditions of local populations. Yet understanding of these impacts is very limited. The main purpose of this project is to analyse how the relationship between populations living in areas of conflict and armed non-state actors controlling or contesting those areas results in forms of local governance and order, and how these in turn affect the access to and effectiveness of livelihoods. The study is based on comparative qualitative and quantitative empirical work in Colombia, India, Lebanon, Niger and South Africa. Improving the understanding of these forms of governance and order has important implications. Theoretically, it provides important micro foundations to understand the duration and termination of violent conflict. At the policy level, understanding how different actors operate and influence local conflict dynamics is important for creating the space for interventions to engage with a range of actors, views and local realitie